The Rapture [videorecording (DVD)] - Tolkin, Michael; Newman, Thomas, 1955-; Bazelli, Bojan; Rogers, Mimi; Duchovny, David; Bauchau, Patrick; Cullum, Kimberly; Hanauer, Terri, 1964-; Williams, Dick Anthony; LeGros, James; Davis, Carole; Patton, Will (New Line Home Entertainment, 2004)
A young woman, so unhappy with her life that she attempts suicide, undergoes a religious conversion when she is comforted by members of a cult. Her involvement with the cult leads to a frightening and ultimately tragic denouement.